2018
DOI: 10.1111/iju.13718
|View full text |Cite
|
Sign up to set email alerts
|

Oral 5‐aminolevulinic acid‐mediated photodynamic diagnosis using fluorescence cystoscopy for non‐muscle‐invasive bladder cancer: A multicenter phase III study

Abstract: These findings confirm the diagnostic efficacy and safety of photodynamic diagnosis with 20 mg/kg of oral 5-aminolevulinic acid, and show that transurethral resection of bladder tumors with a fluorescent light source using oral 5-aminolevulinic acid is well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 28 publications
3
57
2
1
Order By: Relevance
“…In Japan, oral‐PDD‐TUR‐BT was approved by the Ministry of Health, Labor, and Welfare in December 2017 based on several clinical trials, which demonstrated the safety and effectiveness of oral‐PDD‐TUR‐BT . It has been reported that PDD exhibits sensitivity and specificity of 79.6% and 80.6%, respectively, for detecting NMIBC . In addition, luminescence is frequently detected when PDD is used to examine tangential tissue walls and inflamed tissue at sites affected by bladder cancer .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, oral‐PDD‐TUR‐BT was approved by the Ministry of Health, Labor, and Welfare in December 2017 based on several clinical trials, which demonstrated the safety and effectiveness of oral‐PDD‐TUR‐BT . It has been reported that PDD exhibits sensitivity and specificity of 79.6% and 80.6%, respectively, for detecting NMIBC . In addition, luminescence is frequently detected when PDD is used to examine tangential tissue walls and inflamed tissue at sites affected by bladder cancer .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, TUR‐BT has been widely used in combination with PDD (PDD‐TUR‐BT) to treat NMIBC . According to guidelines issued in 2018 by the European Association of Urology and the National Comprehensive Cancer Network, PDD‐TUR‐BT involving the intravesical injection of an aminolevulinic acid, that is either 5‐ALA or hexaminolevulinic acid, is recommended for NMIBC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical benefit of PDD‐assisted TURBT with 5‐ALA is evident from several studies . We carried out a phase III study of this new diagnostic technique in Japan using a preoperative oral administration of 20 mg/kg 5‐ALA .…”
mentioning
confidence: 99%
“…The clinical benefit of PDD‐assisted TURBT with 5‐ALA is evident from several studies . We carried out a phase III study of this new diagnostic technique in Japan using a preoperative oral administration of 20 mg/kg 5‐ALA . On the basis of the reported high diagnostic accuracy and good safety profile, oral 5‐ALA has been approved as an intraoperative diagnostic drug in Japan since December 2017.…”
mentioning
confidence: 99%